Stimuli-responsive gelators from carbamoyl sugar derivatives and their responses to metal ions and tetrabutylammonium salts. Issue 66 (4th November 2020) - Wang, Dan; Chen, Anji; Morris, Joedian; Wang, Guijun
Abstract : Sugar based gelators for both metal ions and tetrabutylammonium salts. Abstract : Carbohydrate-based low molecular weight gelators (LMWGs) are interesting compounds with a variety of applications. In this research, a library of nineteen carbamate derivatives of N -acetyl-d -glucosamine were synthesized and characterized, and several derivatives were found to be effective LMWGs. They formed gels in pump oils as well as mixtures of water with ethanol or water with DMSO. The structures of the carbamoyl chains played an important role in the gelation properties, short chain aliphatic derivatives and phenyl carbamates formed gels in more solvents than certain aromatic and dimeric carbamates. The phenyl carbamate gelator was also selected for the encapsulation of naproxen sodium, and the drug slowly diffused from the gel to the aqueous phase as indicated by UV-vis spectroscopy. In addition, we also found that the p -methoxyl benzyl carbamate derivative showed interesting stimuli-responsive gelation properties in the presence of metal salts and tetrabutylammonium salts. The gels were characterized using optical microscopy, scanning electron microscopy, rheology and other methods. The self-assembling mechanisms of the gelators were studied using 1 H NMR spectroscopy. The preparation, characterization, and molecular assembling properties of these compounds are reported. The results obtained from this study are useful for the design of other LMWGs and the sugar derivatives can be explored for different biological applications. The formation of spontaneous ionic gels can be applicable for a plethora of applications including catalysis and environmental remediation.